Survival Plant Inventory On The Singgalang Mountain Pathway - Rizki Nanda Putra Withman; Des M (Universitas Negeri Padang, 2020)
Mount Singgalang is one of the mountains in West Sumatra that is often climbed because it has natural beauty. Most climbers only have the determination and intention to make the climb and not understand the sciences in climbing. One part of survival is knowledge about wild plants that can be used for consumption and can also be used as medicine (herbal plants). This research was conducted to find out the types of plants that can be consumed on the Mount Singgalang hiking trail via Pandai Sikek. This research is a descriptive study using the survey method. The technique of collecting samples by inventorying samples in the field and continued identification and manufacture of herbariums at the Botanical Laboratory of FMIPA UNP. The data obtained is presented in the form of tables, where the plants are obtained at several elevation points, namely, 1670 masl, 1815 masl, 2137 masl, 2530 masl, 2667 masl. Based on the results of research conducted on Mount Singgalang, 9 species were found grouped into 6 families. Inventory of plant data can be grouped into several plants that can be consumed for food.Katakunci : Inventarisasi, Survival, Gunung Singgalang.